Validation of a new scale Evaluating the Personal, Interpersonal and Contextual dimensions of growth through learning – the EPIC scale. (September 2022) - Obsuth, Ingrid; Brown, Ruth Harriet; Armstrong, Ruth
Abstract: Learning Together (LT) is a co-educational programme that brings prison- and university-based students together to study in ways that encourage growth via transformative learning. Interviews with participating students identified six core factors that they believed LT fosters: self-efficacy, interpersonal-efficacy, self-esteem, perspective-taking, future orientation, and social cohesion. The current study aimed to validate a new scale Evaluating the Personal, Interpersonal, and Contextual dimensions of growth through LT (the EPIC scale) to assesses all of them concurrently. University students (N = 852) completed the EPIC scale, the questionnaires from which it was adapted, and additional measures to ascertain construct, convergent and discriminant validity. Analyses identified seven-factors, where self-efficacy parsed into 'Perseverance' and 'Drive'. Each of the factors showed relations with the original and related measures. The EPIC scale is a psychometrically sound assessment tool that may be reliably used to track the personal development of students across their participation in learning programmes, including LT. Highlights: The EPIC scale is a valid and reliable assessment tool. The EPIC scale consists of seven factors. Each factor of the EPIC scale reliably tracks a different aspect of students growth. The EPIC scale was developed through theoretical and empirical inquiry.